Prognostic Value of Centrosome Replication-Related Genes in Prostate Cancer Based on Transcriptomic and Mendelian Randomization - Qizhong Lu; Yufan Wu; Qiwei Yu; Jun Ouyang (American Journal of Men's Health)
Prostate cancer (PCa) is a significant global health concern, with its incidence and mortality rates projected to rise due to population aging. In this study, we utilized PCa transcriptome data from public databases and applied bioinformatics methods to identify three prognostic genes ( CDC20 , RAD51 , and TTK ) related to centrosome duplication in PCa. CDC20 is involved in cell cycle regulation, RAD51 in deoxyribonucleic acid double-strand break repair, and TTK in spindle assembly checkpoint function and cell proliferation. We constructed a risk model and a nomogram model, both demonstrating moderate to good predictive performance with area under the curve values ranging from 0.611 to 0.765 at different time points. Gene set enrichment analysis revealed that these genes were enriched in 64 pathways, including the cell cycle pathway, which is dysregulated in cancer. Furthermore, we analyzed the immune microenvironment and identified 13 differential immune cells and 13 differential immune checkpoints between high- and low-risk groups, providing insights into potential immunotherapy targets for PCa. In conclusion, this study contributes to a deeper understanding of PCa pathogenesis and lays important theoretical and experimental foundations for developing new diagnostic markers and treatment strategies. Future research requires more clinical samples and continued monitoring of the mechanism of these genes in PCa.